Comparative evaluation of the effectiveness of XP-endo Finisher and passive ultrasonic activation on dentinal tubule penetration of irrigation solution: A confocal laser scanning microscopy study - Ajay Singh Rao; Shreya Bhor; Unnati Shah (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this in vitro study was to comparatively evaluate the effectiveness of XP-endo Finisher and passive ultrasonic (PU) activation on dentinal tubule penetration of irrigation solution: A confocal laser scanning microscopy study. Materials and Methods: Forty extracted single-rooted human mandibular canines and premolars were instrumented up to size 40/06 taper and randomly divided into 2 groups (n = 20) based on the activation technique of final irrigation solution into Group A: PU activation and Group B: XP-endo Finisher activation. In each group, 5 ml of 5% NaOCl labeled with fluorescent dye was used during activation as the final irrigation solution. Specimens were sectioned at 2, 5, and 8 mm from the apex and examined under confocal microscope to calculate the dentinal tubule penetration area. Data were analyzed using Tukey's post hoc tests (P = 0.05). Results: PU activation exhibited a significantly higher penetration area than XP-endo Finisher activation (P < 0.05). In addition, at coronal, middle, and apical thirds, all regions of PU activation had significantly higher penetration than XP-endo Finisher activation. Statistically significant differences were found between each root canal third (coronal > middle > apical) (P < 0.001). Conclusion: The PU activation is more effective than XP-endo Finisher in terms of irrigant penetration into the dentinal tubules.